Una nuova geografia per le aree agricole italiane affette da vincoli naturali - Lupia, Flavio; Fraschetti, Luca; Fantappiè, Maria; Storti, Daniela (GEOmedia, 2020)
This contribution reports the results of the application of the JRC guidelines to identify Italian agricultural areas, other than mountain areas, facing significant natural constraints (Areas with Natural Constraints – ANCs). Spatial analysis has been carried out to integrate climatic, soil, terrain and agricultural data. The latter were integrated with administrative boundaries to classify each municipality as ANC if at least one biophysical criterion was relevant. We report maps, tables and graphs of the Italian ANCs defined by biophysical criteria depicting the new geography where agricultural activities might face significant natural constraints.